Mid-term evaluation of CIDA project 540/13127. Technical cooperation on agriculture - IICA - Ritchie, John (2017)
After the Fourth Regular Meeting of the Inter-American Board of Agriculture, held in Ottawa in 1987, where the concept of a Joint Action Plan for Agricultural Reactivation in Latin America and the Caribbean was approved, Canada began to seriously consider the possibility of setting up an Assistance Program for the Inter-American Institute for Cooperation on Agriculture. The project under review, Agricultural Technical Assistance IICA, was approved in April 1988 with a value of $ 4.57 million. The general objective was to support the development of programs and activities in the five areas of concentration defined by the Medium Term Plan, 1987-91, and to provide greater links between IICA and the institutions and the Canadian experience. His Agriculture Canada was designated as the Canadian Executor